Impact of data privacy and confidentiality on developing telemedicine applications: a review participates opinion and expert concerns - Zaidan, B.B.; Zaidan, A.A.; Mat Kiah, M.L. (2011)
Telemedicine referred to any health care delivery application using an active media such as internet, mobile platforms, or satellites to communicate the parties. Telemedicine can be as simple as patient-doctors phone call, or as complex as the remote surgeries (telesurgery). Telemedicine applications required highly secured systems. In this study we will review the impact of data privacy and confidentiality on developing telemedicine applications. Moreover, we will support this review by short survey on 130 participates to support the literature evidence. Â© 2011 Asian Network for Scientific Information.